Arctic curve of the free-fermion six-vertex model with reflecting end boundary condition. (8th November 2019) - Passos, I R; Ribeiro, G A P
Abstract: We consider the six-vertex model with reflecting end boundary condition. We study the asymptotic behavior of the boundary correlations. This asymptotic behavior is used as an input into the tangent method in order to derive analytically the arctic curve at the free fermion point. The obtained curve is a semicircle, which is in agreement with previous Monte Carlo simulations.